PERAN DAN TANGGUNG JAWAB NOTARIS DALAM PEMBUATAN AKTA PERJANJIAN KREDIT USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA PT. BANK MANDIRI (PERSERO) TBK DI KOTA SURABAYA - , Paulina Astarani Widya Yunaresti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to examine the roles and responsibilities of notaries in the making of particular Credit Agreement, especialy to Credit Micro, Small and Medium Enterprises (SMEs) in Bank Mandiri Surabaya city, whether it is in accordance with the UUJN and the Code of Ethic of Notary. This research also examines the various forms of the obstacles encountered by the notary in the city of Surabaya and how the notary attempts to overcome the various obstacles. This research is a juridical and empirical research, is research which uses primary data is data taken directly from the community, supported by secondary data. To complement and support the data obtained from literature research, field research conducted to obtain primary data interviews were conducted directly to the parties associated with this problem. All data were analyzed with qualitative methods. Results of this research are: (1) Roles and Responsibilities under the UUJN and the the Code of Ethic of Notary is bound to run all the provisions of the legislation. Role in the notary deed notarized credit agreement includes deed and deed under hand made by a notary. The kind of responsibilities of notary may be a form of sanctions for any violations of these provisions. However, in this case never happens to the notary a civil lawsuit because the creditors (Bank Mandiri) and debtors (customers Mandiri bank loans) do not feel aggrieved by the offense that might be done by a notary. (2) Obstacles encountered by the notary for this can be caused by various factors, such as moral and ethical attitudes that hinder the performance of work notary himself, bureaucratic regulation in areas that frequently change, and in relation to the making of bank credit agreement sometimes encountered attitude of banks and credit customers who are not pro-active with the notary.